Metode Azimuth Kiblat dan Rashdul Kiblat dalam Penentuan Arah Kiblat - Ila Nurmila (Fakultas Syari'ah | Institut Agama Islam Darussalam | IAID | Ciamis, Jawa Barat, Indonesia, 2020)
This article examines the methods of determining the Qibla direction, namely the Qibla azimuth and Rashdul Qibla methods. In this research, the writer tries to describe and interpret the concept of Qibla direction and the concept of Qibla azimuth and Rasdul Qibla in astronomical formulations. The Qiblah problem is nothing but talking about the direction of praying exactly to the Kaaba in Mecca from a point where it is located one line in the great circle of the earth and is the closest distance between the point of place and the Kaaba. Given that every point on the Earth’s surface is on the surface of the Earth’s sphere, then the calculation uses spherical trigonometry. To know the Qibla direction correctly, it is necessary to do calculations and measurements. In calculating and measuring the Qibla direction, there are several methods, and the results are quite varied.